2022
DOI: 10.1007/s11747-022-00860-z
|View full text |Cite
|
Sign up to set email alerts
|

Corporate lobbying and product recalls: an investigation in the U.S. medical device industry

Abstract: While corporate political activity is increasing, its effects on firms’ marketing-relevant outcomes have been largely overlooked in the literature. We propose that corporate lobbying will decrease a firm’s emphasis on product safety and, in turn, increase its product recalls. We further propose that the positive indirect effect of corporate lobbying on a firm’s product recalls via lower emphasis on product safety will be moderated by the firm’s (a) CEO’s functional background and (b) focus on radical (vs. incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In industries where regulators wield more influence than consumers, firms' countering strategies would likely focus on regulators and devote significant resources to influence the regulatory process (Krueger, 1974; Mahmood & Rufin, 2005; Oosterhuis‐Blok & Graafland, 2022; Peltzman, 1976; Singh & Grewal, 2022; Stigler, 1971), which explains the prevalence of pharmaceutical lobbying (c.f., Ahen, 2017; Barber IV & Diestre, 2019; Goldacre, 2014; Ozcan & Gurses, 2018). A recent study has found that lobbying regulators indeed reduce medical device companies' emphasis on product safety (Giannetti & Srinivasan, 2022). Moreover, the specific structure of the industry increases the chance of “regulatory capture,” i.e., when the regulatory agency is dominated by the special interest groups that the agency is supposed to regulate (Abraham, 2008; Dal Bó, 2006; Laffont & Tirole, 1991; Nocera, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In industries where regulators wield more influence than consumers, firms' countering strategies would likely focus on regulators and devote significant resources to influence the regulatory process (Krueger, 1974; Mahmood & Rufin, 2005; Oosterhuis‐Blok & Graafland, 2022; Peltzman, 1976; Singh & Grewal, 2022; Stigler, 1971), which explains the prevalence of pharmaceutical lobbying (c.f., Ahen, 2017; Barber IV & Diestre, 2019; Goldacre, 2014; Ozcan & Gurses, 2018). A recent study has found that lobbying regulators indeed reduce medical device companies' emphasis on product safety (Giannetti & Srinivasan, 2022). Moreover, the specific structure of the industry increases the chance of “regulatory capture,” i.e., when the regulatory agency is dominated by the special interest groups that the agency is supposed to regulate (Abraham, 2008; Dal Bó, 2006; Laffont & Tirole, 1991; Nocera, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…They argue that regulation has failed miserably in preventing discrimination against black consumers, implying that the market's hand is visible and white instead. In a more direct indictment, Giannetti and Srinivasan (2022) show that corporate lobbying reduces firms' attention to product safety, thereby endangering consumers and increasing product recalls. Similarly, Vadakkepatt et al (2022) argue that lobbying often furthers a firm's interest among regulators to the detriment of its market effectiveness.…”
Section: Capitalist Nexus As a Force Preventing Effective Regulationmentioning
confidence: 99%